ANALISIS FUNGSI BORDA UNTUK MENGETAHUI TINGKAT PENGETAHUAN TERHADAP KURIKULUM ABAD 21 - Elva Susanti; Anggia Arista (JURNAL REKAYASA SISTEM INDUSTRI, 2019)
This study aims to determine the extent of teacher knowledge about the 21st century curriculum by using the BORDA function. There are four skills and abilities namely communication, collaboration, critical and creative. The sample used was junior high and vocational school teachers in Batam. The results of his research communication skills have a greater percentage than other skills, namely for junior high school teacher communication knowledge by 43% and vocational school by 34%. Whereas in the SWOT analysis skills and communication skills are the strengths that both have a higher value than other indicators, both junior high and vocational high schools.